Health and environmental co-benefits of city urban form in Latin America: an ecological study. (April 2021) - Avila-Palencia, Ione; Sánchez, Brisa N; Rodríguez, Daniel A; Perez Ferrer, Carolina; Miranda, J Jaime; Gouveia, Nelson; Bilal, Usama; Useche, Andrés F; Wilches-Mogollon, Maria A; Sarmiento, Olga L; Diez Roux, Ana V
Abstract: Background: Urban design features are often studied in relation to health and behavioural outcomes. They can also have major implications for environmental outcomes. However, the impact of these features on both health and environmental outcomes (co-benefits) is rarely examined. We investigated how urban landscape and street design profiles are related to jointly occurring health and environmental outcomes in Latin America cities. Methods: We used data from the Salud Urbana en América Latina (SALURBAL) project, which has compiled and harmonised data on built environment, environmental exposures, and health outcomes for 370 cities in 11 countries: Argentina, Brazil, Chile, Colombia, Costa Rica, El Salvador, Guatemala, Mexico, Nicaragua, Panama, and Peru. Eight city profiles were identified using finite mixture models. Four urban-landscape profiles were defined measuring patch (contiguous area of urban development) fragmentation, shape, and isolation, and four street-design profiles were defined using street connectivity, length, and directness. Multilevel regression models were used to assess associations between the city profiles and several health and environmental outcomes. Findings: Our preliminary results show that compared with the urban-landscape profile labelled scattered pixels (comprising low fragmentation, compact shape, and high isolation), the proximate-stones profile (moderate fragmentation, irregular shape, and moderate isolation) had significantly higher levels of PM2·5 and nitrogen dioxide (NO2 ), and the proximate-inkblots profile (moderate-to-high fragmentation, complex shape, and moderate isolation) had significantly higher levels of violence-related deaths. Compared with the labyrinthine street design profile (low connectivity, moderate length, and moderate directness), the semi-hyperbolic grid (moderate connectivity, moderate length, and moderate directness) and spiderweb (high connectivity, low length, and moderate directness) profiles had significantly higher levels of PM2·5 and NO2, whereas the hyperbolic grid profile (moderate connectivity, high length, and low directness) had significantly higher levels of NO2 and lower levels of obesity. Interpretation: Identifying how city profiles are related to environment and health outcomes can shed light on the urban policies that could have the greatest environment and health co-benefits. Funding: The SALURBAL/Urban Health in Latin America project is funded by the Wellcome Trust (205177/Z/16/Z).